Application of Talking Stick Learning Model to Improve Students' Positive Attitude and Learning Achievement in the Subject of Heat - Muhsin Muhsin (Universitas Muhammadiyah Makassar, 2019)
The research included classroom action research that was conducted on 2018 the purpose of research was to improve learning achievement and positive attitudes of the seventh E grade students at thirteen Bontoa junior high school in science learning. This classroom action research was conducted at thirteen Bontoa junior high school in seventh E grade in the first semester on 2018/2019 academic year. The research consisted of two cycles, the first cycles consisted of two actions and the second cycles also consisted of two action. The procedure carried out in research cycle consisted of planning, implementation, observation and reflection. For getting data used observation sheets and the results test scores in each cycle. The data analysis technique used descriptive analysis and qualitative analysis. The result showed the application of talking stick learning model to improve positive attitudes and learning achievement of the main science of kalor subject in VII.E grade students of 13 Bontoa Junior High Scholl in Maros District.Keywords: Talking Stick Learning Model, Positive Attitude, Learning AchievementPenelitian ini termasuk Penelitian Tindakan Kelas yang dilaksanakan pada tahun 2018. Tujuan dari penelitian ini adalah untuk meningkatkan prestasi belajar dan sikap positif siswa kelas VII.E pada SMP Negeri 13 Bontoa dalam pembelajaran IPA. Penelitian Tindakan Kelas ini dilaksanakan di SMP Negeri 13 Bontoa pada siswa kelas VII.E semester 1 tahun pelajaran 2018/2019. Penelitian ini terdiri dari dua siklus. Siklus pertama terdiri dari dua tindakan dan siklus kedua juga terdiri dari dua tindakan. Prosedur yang dilaksanakan pada setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Untuk mendapatkan data digunakan lembar observasi dan hasil nilai tes pada setiap siklus. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran talking stick dapat meningkatkan prestasi belajar dan sikap positif siswa kelas VII.E SMP Negeri 13 Bontoa dalam pembelajaran IPA khususnya materi tentang Kalor.Kata kunci: Model Pembelajaran Talking Stick, Sikap Positif, Prestasi Belajar